1998
DOI: 10.1046/j.1365-2222.1998.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CLA+ lymphocytes from children with atopic dermatitis contain an increased percentage of cells bearing staphylococcal‐related T‐cell receptor variable segments

Abstract: Our data indicate that circulating skin-homing T cells of patients with active atopic dermatitis contain an increased percentage of cells bearing TCR Vbeta segments related with Staphylococcus aureus. Staphylococcus superantigens may therefore trigger expansion or at least circulation of appropriate CLA+ T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…In addition, Torres observed a significantly increased percentage of CLA þ Vb5.1 þ T cells in children with AD compared with normal controls (Torres et al, 1998). Most other studies that evaluated the Vb repertoire in AD have, however, not shown an increase in Vb5.1 in the skin (Neuber et al, 1996;Yudate et al, 1996;Bunikowski et al, 2000), nor blood of AD patients (Strickland et al, 1999;Bunikowski et al, 2000;Davison et al, 2000) compared to normal controls, and Neuber et al (1996) actually found a significantly decreased percentage of Vb5.1 þ T cells in the skin of AD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Torres observed a significantly increased percentage of CLA þ Vb5.1 þ T cells in children with AD compared with normal controls (Torres et al, 1998). Most other studies that evaluated the Vb repertoire in AD have, however, not shown an increase in Vb5.1 in the skin (Neuber et al, 1996;Yudate et al, 1996;Bunikowski et al, 2000), nor blood of AD patients (Strickland et al, 1999;Bunikowski et al, 2000;Davison et al, 2000) compared to normal controls, and Neuber et al (1996) actually found a significantly decreased percentage of Vb5.1 þ T cells in the skin of AD.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the skin of patients with AD is often colonized by enterotoxin-producing strains of Staphylococcus aureus, and these superantigenic toxins are capable of skewing the Vb subfamily repertoire in skin-homing T cells as well as increasing expression of the skin-homing receptor, CLA (Leung et al, 1995;Neuber et al, 1996;Torres et al, 1998;Dworzak et al, 1999;Strickland et al, 1999;Bunikowski et al, 2000;Davison et al, 2000;Zollner et al, 2000;Breuer et al, 2002). Even with healthy individuals, molecular studies have shown differences in Vb family expression in skin samples compared with the blood, suggesting an effect of the microenvironment of the T cell repertoire (Dunn et al, 1993;Ahangari et al, 1996;Menssen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…44, 89 In addition, increased S. aureus colonization, as evidenced by increased T-cell receptor (TCR) Vβ expression on CLA + T-cells, 90 underdeveloped IL-22, reduced IL-17 and suppressed IFN-γ, all considered protective cytokines against pathogens, 9198 might orchestrate the immune milieu, rendering AD children more susceptible to skin infections. 99, 100 …”
Section: Discussionmentioning
confidence: 99%
“…Most T cells infiltrating inflammed skin are CLA-positive, whereas CLA is not expressed on the T cells present in other inflammatory tissues. Previous studies indicated that AD patients had a higher percentage of T cells bearing SsAg-reactive TCRVβ in the peripheral blood CLA + T cells than healthy subjects [106,107]. Leung et al [108] showed that IL-12 is the most important cytokine in the induction of CLA expression on T cells.…”
Section: Expansion Of Skin-homing Cutaneous Lymphocyteassociated Antimentioning
confidence: 99%